Улога нивоа серумских ITF, IBA-1 и калгранулина Б у раној дијагностици и прогнози рака грлића материце: Нивои серума ИТФ, ИБА-1 и калгранулина Б код рака грлића материце - Zhou, Yuxiang; Liu, Jianwei; He, Jiayi; Zhang, Mingying; Zou, Xuehong (Journal of Medical Biochemistry, 2026)
[Objective] To explore the clinical value of serum Intestinal Trefoil Factor (ITF), Ionized Calcium-Binding Adapter Molecule 1 (IBA-1), and Calgranulin B levels in the early auxiliary diagnosis and prognostic evaluation of cervical cancer. [Methods] The cervical cancer group consisted of 256 patients who received a cervical cancer diagnosis at this hospital between January 2023 and June 2024. 150 people who were diagnosed with cervical intraepithelial neoplasia (CIN) at this hospital within the same time period made up the CIN group. 90 women who underwent health checks at this facility throughout the same time period made up the healthy control group. The diagnostic effectiveness of serum ITF, IBA-1, and Calgranulin B levels in patients with cervical cancer, as well as their correlations with clinical indicators and prognosis, were examined, as were changes in these levels in each group. [Results] The cervical cancer group’s blood ITF, IBA-1, and Calgranulin B levels were noticeably higher than those of the CIN group and the healthy control group. Compared to the healthy control group, the CIN group’s serum ITF, IBA-1, and Calgranulin B levels were considerably higher (P<0.05). When diagnosing cervical cancer, serum ITF, IBA-1, and Calgranulin B levels are highly valuable. When all three signs were detected together, the sensitivity was 89.4% and the specificity was 97.6%, and 0.961 was the receiver operating characteristic curve’s area under the curve, which was significantly greater than that of ITF (Z=4.620, P<0.05), IBA-1 (Z=4.167, P<0.05), and Calgranulin B (Z=5.210, P<0.05) alone in independent testing. Serum ITF, IBA-1, and Calgranulin B levels were significantly higher in patients with poorly differentiated, clinical stage II, HPV-positive cervical cancer with lymph node metastases than in patients with moderately differentiated, clinical stage I, HPV-negative cervical cancer without lymph node metastases. These differences were statistically significant (P<0.05). However, there were no statistically significant differences in the levels of serum ITF, IBA-1 or Calgranulin B among cervical cancer patients of different ages, pathological types, maximum tumor diameters, depths of myometrial invasion, vascular invasion and nerve invasion (P>0.05). Serum ITF, IBA-1, and Calgranulin B levels in the nonsurviving group were substantially higher than those in the surviving group at the 1-year follow-up (P<0.05). [Conclusion] The levels of serum ITF, IBA-1 and Calgranulin B have high clinical value in the diagnosis and prognostic evaluation of cervical cancer. The combined detection of these three indicators is helpful for improving the auxiliary diagnostic efficacy of cervical cancer.